In vitro Synergy of Polyphenolic Extracts From Honey, Myrtle and Pomegranate Against Oral Pathogens, S. mutans and R. dentocariosa - Sateriale, Daniela; Facchiano, Serena; Colicchio, Roberta; Pagliuca, Chiara; Varricchio, Ettore; Paolucci, Marina; Volpe, Maria Grazia; Salvatore, Paola; Pagliarulo, Caterina (Frontiers in Microbiology, 2020)
The increasing incidence of oral diseases, the wide spread of antimicrobial resistance and the adverse effects of the conventional antibiotics, need alternative prevention and treatment options to counteract oral pathogens. In this regard, our study aims to evaluate the antibacterial activity of polyphenolic 1extracts prepared from acacia honey, myrtle leaves and pomegranate peel against cariogenic bacteria, as Streptococcus mutans and Rothia dentocariosa. The chemical-physical parameters of acacia honey and the RP-HPLC polyphenolic profile of pomegranate peel extracts have been previously described in our studies, while the characterization of myrtle extracts, performed by HPLC analysis, is reported here. All the extracts were used singly and in binary combinations to highlight any synergistic effects. Moreover, the extracts were tested in association with amoxicillin to evaluate their ability to reduce the effective dose of this drug in vitro. The values of minimal inhibitory concentrations and minimal bactericidal concentrations have been used to quantitatively measure the antibacterial activity of the single extracts, while the fractional inhibitory concentration index has been considered as predictor of in vitro anticariogenic synergistic effects. Finally, time-kill curve method allowed to evaluate the bactericidal efficacy of combined extracts. The microbiological tests suggest that acacia honey, myrtle and pomegranate extracts are able to inhibit the cariogenic bacteria, also with synergistic effects. This study provides useful and encouraging results for the use of natural extract combinations alone or in association with antibiotic (adjuvant therapy) as a valid alternative for the prevention and treatment of oral infectious diseases.